2007
DOI: 10.1038/nn1872
|View full text |Cite
|
Sign up to set email alerts
|

Musical experience shapes human brainstem encoding of linguistic pitch patterns

Abstract: Music and speech are very cognitively demanding auditory phenomena generally attributed to cortical rather than subcortical circuitry. We examined brainstem encoding of linguistic pitch and found that musicians show more robust and faithful encoding compared with nonmusicians. These results not only implicate a common subcortical manifestation for two presumed cortical functions, but also a possible reciprocity of corticofugal speech and music tuning, providing neurophysiological explanations for musicians' hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
812
9
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 831 publications
(868 citation statements)
references
References 15 publications
42
812
9
5
Order By: Relevance
“…One mechanism involves specialized neurons that are tuned to relevant aspects of sensory input, or attenuate irrelevant aspects [e.g., Gordon and O'Neil, 2000;Rauschecker et al, 1995;Wong et al, 2007b]. In the auditory system, which subserves both speech and music processing, evidence suggests that low-level neurons are tuned to basic acoustic properties such as center frequency (CF) and frequency modulation (FM) (''information-bearing elements'' or IBEs), while high-level neurons are sensitive to relevant parts and combinations of IBEs, which carry species-specific communicative functions [Suga, 1995;Suga et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism involves specialized neurons that are tuned to relevant aspects of sensory input, or attenuate irrelevant aspects [e.g., Gordon and O'Neil, 2000;Rauschecker et al, 1995;Wong et al, 2007b]. In the auditory system, which subserves both speech and music processing, evidence suggests that low-level neurons are tuned to basic acoustic properties such as center frequency (CF) and frequency modulation (FM) (''information-bearing elements'' or IBEs), while high-level neurons are sensitive to relevant parts and combinations of IBEs, which carry species-specific communicative functions [Suga, 1995;Suga et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, an increasing number of scientists have sought to understand what underlies this seemingly ubiquitous benefit of musical training. We now know that the musician's brain has functional adaptations for processing pitch and timbre (3)(4)(5)(6) as well as structural specializations in auditory, visual, motor, and cerebellar regions of the brain (7)(8)(9). Some studies also suggest that the interplay between modalities is stronger in musicians (10) and, in the case of conductors, that improved audiovisual task performance is related to enhanced activity in multisensory brain areas (11).…”
mentioning
confidence: 99%
“…Measurements of the speech-evoked onset response and FFR, such as peak latencies and spectral amplitudes, have been studied extensively. In addition, it has been shown that these two main features of the brainstem response are influenced by viewing phoneme articulations and auditory training (6,12,37,38), thus making these responses suitable tools for the investigation of musicianship effects.…”
mentioning
confidence: 99%
“…Brainstem responses in musicians relative to nonmusicians have recently been shown to be faster, larger, and more reliable when encoding the periodicity of speech and music (9,10). Importantly, the enhanced auditory processing skills transferred from music to speech (11).…”
mentioning
confidence: 99%